2017
DOI: 10.1007/s12035-017-0792-z
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation Therapy Improves Acute Inflammatory Response in Mice: the Role of Cannabinoid Receptors/ATP-Sensitive K+ Channel/p38-MAPK Signalling Pathway

Abstract: Although photobiomodulation therapy (PBM) has been applied clinically for the treatment of pain and inflammation, wound healing, sports and soft tissue injuries, as well as to repair injured spinal cords and peripheral nerves, it remains unclear which molecular substrates (receptor) are implicated in the cellular mechanisms of PBM. Here, we reported that PBM (660 nm, 30 mW, 0.06 cm, 50 J/cm, plantar irradiation) significantly inhibited carrageenan-induced paw oedema, but not noxious thermal response, through p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 84 publications
0
24
0
1
Order By: Relevance
“…34,35 Previous studies also revealed that K ATP channel activators produced their antioxidant, anti-inflammation, antiapoptotic effects by causing significant decreases in IL-6 production. 36,37 Other studies showed that IL-6 inhibited eNOS expression in acute-phase inflammatory response either directly or through activation of IL-6/STAT3 pathway. [38][39][40] Besides, prior investigations showed that activation of TRPV1 by capsaicin resulted in significant inhibition of constitutive and IL-6-induced activation of STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Previous studies also revealed that K ATP channel activators produced their antioxidant, anti-inflammation, antiapoptotic effects by causing significant decreases in IL-6 production. 36,37 Other studies showed that IL-6 inhibited eNOS expression in acute-phase inflammatory response either directly or through activation of IL-6/STAT3 pathway. [38][39][40] Besides, prior investigations showed that activation of TRPV1 by capsaicin resulted in significant inhibition of constitutive and IL-6-induced activation of STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the fact that infrared LED was effective against mechanical and thermal hypersensitivity to cold on each day of treatment, which is clinically interesting, raises a precedent that would justify investment in research studying patients affected by this syndrome. Additionally, the therapeutic effects both on the reduction of mechanical hypersensitivity and on the cold thermal test suggest the activation of different receptor populations and neural fibers involved in the process of pain, such as those suggested by previous studies …”
Section: Discussionmentioning
confidence: 53%
“…Additionally, the therapeutic effects both on the reduction of mechanical hypersensitivity and on the cold thermal test suggest the activation of different receptor populations and neural fibers involved in the process of pain, such as those suggested by previous studies. 12,63,64 It is important to further investigate the type of device used and the location of LED application. In this study, we used a device with a multiple-LED array, and the site of application was the entire body of the animal, which is primarily how this study differs from the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ATP1B4 is not only the source gene of TCONS_00279168 but also its target gene. ATP1B4 is a member of ATPase Na+/K+ transporting family, which is believed to contribute to the activity of the MAPK signaling pathway, which is well supported by the studies in humans [ 53 , 54 ]. Furthermore, ATP1B4 , as an important member of ATPase Na+/K+ transporting beta M family, which is involved in the regulation of gene expression level in TGF-β signaling pathway as exemplified by an increase of expression of inhibitory Smad7.…”
Section: Discussionmentioning
confidence: 93%